2011
DOI: 10.3136/fstr.17.121
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rice Properties on Bread Made from Cooked Rice and Wheat Flour Blend

Abstract: Cooked rice bread was made with cooked rice substituted for 0 to 30% of the wheat flour. Eleven rice cultivars were used to clarify the effects of rice properties on specific loaf volume (SLV). The cooked rice bread had higher SLV than the bread without substitution, except for bread made with rice having highamylose content. The maximum specific loaf volume (Max SLV) of cooked rice bread was calculated using SLV loaf volumes. Max SLV was negatively correlated with amylose content and rice hardness, while rice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…However, the wheat flour bread contains low levels of essential amino acids such as lysine and threonine (Cercel et al, 2016;Pallarés et al, 2007;Turfani et al, 2017). In several countries, due to the significant role of a diet based on wheat bread, it has become a habit to enrich flour with nutrients that are limited or absent in this flour, according to the law of each country (Centenaro et al, 2007;Keiko et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, the wheat flour bread contains low levels of essential amino acids such as lysine and threonine (Cercel et al, 2016;Pallarés et al, 2007;Turfani et al, 2017). In several countries, due to the significant role of a diet based on wheat bread, it has become a habit to enrich flour with nutrients that are limited or absent in this flour, according to the law of each country (Centenaro et al, 2007;Keiko et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Rice noodles, a well-known food in Southeast Asian countries, have not been popular in Japan because eating rice noodles is not a dietary habit of the Japanese. Thus, several studies have examined substitution of all or part of wheat flour with rice in bread making, by milling rice grain into flour (Iwashita et al, 2011;Nakamura et al, 2009;Sabanis and Tzia, 2009). However, making rice flour bread with a similar volume to wheat flour bread is difficult because the rice protein does not develop a similar viscoelastic structure to gluten, in which the network retains gases inside the dough during mixing and proofing (Kawamura-Konishi et al, 2013;Marco and Rosell, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the thermal properties, it has been reported that initial pasting and setback viscosities decrease with decreasing particle sizes, with wet milled rice flours that have higher apparent viscosity and smaller particle sizes than dry-milled rice flour showing better properties for making gluten-free rice bread (Song and Shin, 2007). Rice cultivars with intermediate amylose contents, which also are sticky and soft, give bread with high volume (Iwashita et al, 2011). In addition to the cultivar type, germination is also of interest for increasing the nutritional pattern of cereals and pseudocereals (Omary et al, 2012) and because proteolytic enzymes produced during germination could decrease the toxicity of some cereals.…”
Section: Leavened Gluten Free Products: Challenges For Miming Glutenmentioning
confidence: 99%